Renal cell carcinoma in ectopic-pelvic kidney: A rare case with review of literature - Alokour, Radwan Khalid (Turk J Urol, 2018)
The incidence of renal cell carcinoma in a pelvic kidney is rare, and has only been reported in a small number of cases. We report a 50-year-old male patient presented with vague abdominal pain and without hematuria. CT scan showed large heterogeneous soft tissue mass arising from a left pelvic kidney with areas of necrosis measuring 8.4×8.4×7.5 cm. Histopathology after radical nephro-ureterectomy showed grade II clear-cell renal carcinoma. Renal cell carcinoma of ectopic kidney is a rare disease. Even though the presentation might be atypical and challenging, the treatment strategy is still the same as for tumors of orthotopic kidneys.